Is PSA related to serum cholesterol and does the relationship differ between black and white men?. Issue 16 (1st September 2015) - Zapata, Daniel; Howard, Lauren E.; Allott, Emma H.; Hamilton, Robert J.; Goldberg, Kenneth; Freedland, Stephen J.
<x xml:space="preserve">Abstract</x> Background Previously, in prostate cancer‐free men, we found that statin initiation resulted in a 4.1% decline in PSA. This decline in PSA was proportional to the decline in cholesterol, suggesting a link between cholesterol and PSA levels. Whether these associations vary by race has not been explored and therefore we examined the association between pre‐statin serum cholesterol and PSA in black and white prostate cancer‐free men. Methods We conducted a retrospective, cross‐sectional analysis of 1, 163 men (709 white and 454 black) without prostate cancer who initiated a statin between 1994 and 2006. Linear regression was used to test the association between pre‐statin serum cholesterol and PSA levels, adjusting for potential confounders and stratifying by race. Results Black men were younger, had higher low‐density lipoprotein (LDL) and high‐density lipoprotein (HDL) levels (both P < 0.05) and a trend toward higher total cholesterol (P = 0.063). There was no difference in PSA or year of statin prescription by race (P = 0.900 and P = 0.217, respectively). On multivariable analysis, we found a positive correlation between serum PSA and total cholesterol (P = 0.005) and LDL (P = 0.003) in white men, but no association among black men. HDL was not significantly related to PSA levels in black or white men (both P > 0.5). Conclusions Among prostate cancer‐free men about to begin a statin, pre‐statin total cholesterol and LDL were correlated with PSA levels in white, but not black men. If confirmed in future studies, these findings suggest that serum cholesterol may be related to prostate biology, and that this effect may vary by race. Prostate 75:1877–1885, 2015. © 2015 Wiley Periodicals, Inc.